Nutrition, Diet and Healthy Aging - Giacomello, Emiliana; Toniolo, Luana (2022)
Over the last 100 years, the numerous advances in science, the improved sanitary conditions and a decline in poverty have led to an increase in life expectancy. As a result, in the coming years, the number of over-65s will triple, and the over-80s will be the fastest growing portion of the population.However, an increased lifespan is associated with an increase in chronic diseases, such as cardiovascular disease, diabetes, cancer, sarcopenia, and degenerative disorders. Therefore, ideally, increased lifespan should be associated to a better healthspan, which is the period one individual is living in good health.Based on evidence that aging is a multifaceted phenomenon, resulting from one or more failures at the molecular, cellular, physiologic, and functional levels, age-related diseases are difficult therapeutic targets.Data on the correlation between the quality of one's diet and life expectancy, and the application of calorie restriction regimens, or of micronutrients, antioxidants and functional foods in the diet make nutrition, together with exercise, a natural weapon to combat age-related diseases and improve healthspan.